(untitled) (International Seven Journal of Multidisciplinary, 2024)
International financial management plays a crucial role in the global economy, directly influencing the success of multinational companies and the financial stability of countries. This article explores the key concepts, strategies, and challenges involved in financial management in an international context, addressing topics such as global markets, governance, risks, and financial crises. This article offers a detailed overview of the financial practices that underpin global trade and economic development.